THE EFFECT OF PROPRIETARY COSTS TOWARDS THE QUALITY OF SUSTAINABILITY REPORTS MODERATED BY OWNERSHIP STRUCTURE IN THE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD OF 2013-2016 - Nurina Saffanah (Manis: Jurnal Manajemen dan Bisnis, 2020)
This research aims to examine the effect of proprietary costs towards the quality of sustainability reports and the moderating effect of ownership structure on proprietary costs with the quality of sustainability reports. Based on previous research, one of the factors that affect companies to limit disclosure of information which impacting the quality of published sustainability reports is proprietary costs, and to minimize this effect by percentage or total ownership structure. The population in this research is based on data from the Global Reporting Initiative (GRI) for the period of 2013-2016. The samples in this research are determined by purposive sampling technique in which they are 92 sustainability reports from 36 companies listed on the Indonesia Stock Exchange. This research is analyzed using regression analysis and moderated regression analysis. The results show that proprietary costs have a positive effect on the quality of sustainability reports and foreign ownership moderates the negative effects of proprietary costs on the quality of sustainability reports.